Two-photon dissociative ionization of H2 by ultrashort xuv laser pulses (2009)
ABSTRACT: Ab initio calculations of H2 photoionization induced by low-intensity ultrashort xuv laser pulses are reported in the region of two-photon absorption. Our computational approach is based on the solution of the time-dependent Schr¨odinger equation including all electronic and vibrational degrees of freedom. We find that, as one approaches the one-photon ionization threshold, dissociative ionization largely dominates over non dissociative ionization. We show that this behavior is mostly induced by the presence of molecular autoionizing states in this photon energy region.